THE EEFECTIVE OF ERAC PROGRAM FOR EARLY RECOVERY AFTER CESAREAN SECTION CAN THO UNIVERSITY OF MEDICINE AND PHARMACY HOSPITAL AND CAN THO CENTRAL GENERAL HOSPITAL - Lam Duc Tam , Quan Kim Phung, Nguyen Thi To Lan, Mai Nguyen Thanh Truc (South Eastern European Journal of Public Health, 2025)
Background: The ERAC program for early recovery after cesarean section helps women reduce complications, postoperative pain, hospital stay and costs by speeding up the recovery process early in the postoperative period. Objective: Evaluate the results of ERAC (Enhanced Recovery After Cesarean) at Can Tho University of Medicine and Pharmacy Hospital and Can Tho Central General Hospital. Methods: descriptive cross-sectional design with controlled survey of 368 women with indications for caesarean section, randomly selected with the consent of the women. Result: 198/368 (53.8%) applied the ERAC program. The mean age was 29.6 ± 6.1 years old. The mean time to sit up when applying ERAC was 6.83 ± 1.35h compared with 7.52 ± 1.9 hours (p<0.001). The time to walk after surgery was 11.18 ± 2.4h compared with 13.36 ± 4.1h (p<0.001); Normal urination time 10.49 ± 2.3h compared with 11.32 ± 3.3h (p<0.01), normal travel time 35.67 ± 9.7h compared with 39.86 hours ± 4.5 (p<0.001). Pain level after surgery with VAS 4.01±0.7 compared with 4.18±0.7 (p<0.001). Conclusion: The ERAC effective in accelerating the recovery process after cesarean section.